Mini air conditioning design with two levels of thermoelectric cooler module: cooling heat pipe - Irwin Bizzy; Darmawi Darmawi; Agung Mataram; Fadhil Fuad Rachman (Universitas Mercu Buana, 2023)
As the tropical country, the use of air conditioning (AC) in Indonesia is still high. This will affect energy consumption and global warming issue. This study aims to make solution of the AC issue with a design of the mini-AC using thermoelectrical cooler (TEC) technology and determine the output temperature result of the design, then to find out the coefficient of performance (COP) of the TEC cooler. The mini-AC design or method uses two TEC with additional heat sink, heat pipe, and fan to help release temperature to environment. The temperature measuring uses an 11-point thermocouple with real-time data collection using BTM-4208sd logger. The results of the study concluded that the mini-AC could work well even though one of the TECs was below its best performance. The use of heat pipes can help reduce heat quickly from TEC heat side. The best COP of TEC with ideal heat reduction is 0.69 from the upper position (72 W), and the highest at lower position (48 W) with 2.19.